THE LINGUOSTYLISTIC ANALYSIS OF METAPHOR AND METONYMY IN LITERARY TEXTS - Gafforova Iroda Xujayor Kizi; Saidova Dilnoza Meliboy Kizi (Western European Studies, 2025)
This article explores the linguo-stylistic features of metaphor and metonymy as key mechanisms of artistic expression in literary texts. It analyzes their semantic, cognitive, and aesthetic functions, showing how these tropes enrich meaning, shape imagery, and reflect the author’s worldview. The study emphasizes that metaphor and metonymy are not only stylistic ornaments but also fundamental tools of linguistic creativity and human cognition
Keywords: Metaphor; Metonymy; Linguo-Stylistics